Pergeseran Peranan Laki-Laki dalam Masyarakat Minangkabau - Bakti Bakti (Antropologi Indonesia, 1989)
Among the Minangkabau people who practice a matrilineal kinship system, occurs a change in mens's social role, i.e. from a role as an "uncle" (mamak) to a "father" or "husband". This change is caused by various factors, such as religion, education, migration (merantau), and economics. Further, it leads to another change in the Minangkabau's common law, i.e. in the marriage and heredity properties. A problem, however, still exists in the kinship law. The author raises a question whether a change in men's role may influence the Minangkabau's perspective towards the matrilineal kinship system as a basis for their kinship law.